Prevalence and seroepidemiology of Haemophilus parasuis in Sichuan province, China - Wang, Zhenghao (PeerJ, 2017)
Haemophilus parasuis, the causative agent of Glässer’s disease, has been reported as widespread, but little is known about its epidemiology in the Sichuan province of China. The goal of our research is to reveal the prevalence and distribution of H. parasuis in this area. Sampling and isolation were performed across Sichuan; isolates were processed using serotyping multiplex PCR (serotyping-mPCR) and agar gel diffusion (AGD) for confirmation of serovar identity. This study was carried out from January 2014 to May 2016 and 254 H. parasuis field strains were isolated from 576 clinical samples collected from pigs displaying clinical symptoms. The isolation frequency was 44.10%. Statistically very significant differences of infection incidence were found in three age groups (P < 0.01) and different seasons (P < 0.01). Serovars 5 (25.98%) and 4 (23.62%) were the most prevalent, however, non-typeable isolates accounted for nearly 7.87%. In terms of geographical distribution, serovars 5 and 4 were mostly prevalent in west and east Sichuan. The results confirmed that the combined approach was dependable and revealed the diversity and distribution of serovars in Sichuan province, which is vital for efforts aimed at developing vaccine candidates allowing for the prevention or control of H. parasuis outbreaks.